2014
DOI: 10.1063/1.4898756
|View full text |Cite
|
Sign up to set email alerts
|

Fluid interfacial nanoroughness measurement through the morphological characteristics of graphene

Abstract: The interfacial nanoroughness of liquid plays an important role in the reliability of liquid lenses, capillary waves, and mass transfer in biological cells [Grilli et al., Opt. Express 16, 8084 (2008), Wang et al., IEEE Photon. Technol. Lett. 18, 2650), and T. Fukuma et al., 92, 3603 (2007]. However, the nanoroughness of liquid is hard to visualize or measure due to the instability and dynamics of the liquid-gas interface. In this study, we blanket a liquid water surface with monolayer graphene to project the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…The limits of this region corresponded to 0.01 and 0.90 g/cm 3 , which are asymmetrical in the density profile of water, and do not correspond to the values of the so-called "10-90" thicknesses, which corresponds to limiting points in the density profile at 10% and 90% of 𝜌 L * . The final result of Yoon et al 28 calculations did not produce a consistent tendency in the surface tension of water as a function of temperature. We employed this strategy to calculate the surface tension of the Lennard-Jones fluid by eliminating regions of the bulk phases, and the results are summarized in Table I.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…The limits of this region corresponded to 0.01 and 0.90 g/cm 3 , which are asymmetrical in the density profile of water, and do not correspond to the values of the so-called "10-90" thicknesses, which corresponds to limiting points in the density profile at 10% and 90% of 𝜌 L * . The final result of Yoon et al 28 calculations did not produce a consistent tendency in the surface tension of water as a function of temperature. We employed this strategy to calculate the surface tension of the Lennard-Jones fluid by eliminating regions of the bulk phases, and the results are summarized in Table I.…”
Section: Resultsmentioning
confidence: 87%
“…Eliminating at the same time parts of both bulk phases as proposed by Yoon et al 28 does not produce a zero change in 𝛾 * unless you eliminate a very small region in the bulk liquid, but those changes will not reduce considerably 𝜎 k * . These results indicate that the integration over the bulk vapor region does not contribute significantly to the average value of 𝛾 * , neither 𝜎 k * ; the main contribution comes from the region between the interface and a point located between 6.5 and 8.5 reduced units (monolayers) away from the interface, in this zone the liquid density and pressures are uniform and the pressures are equal (bulk).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…This special issue is dedicated to Professor Hsueh-Chia Chang in honor of his 60th birthday and comprised the original contributions that were presented at the conference. The topics cover a wide range of research efforts from both fundamental science and practical applications of microfluidics and nanofluidics, including biosensors and diagnosis for clinical testing, [1][2][3][4] cell and evolution studies, [5][6][7][8][9][10] advanced bioimaging/optical technologies, 11,12 droplet microfluidics, 13,14 bilayer lipid membrane, 14,15 micro-and nanofabrications, [16][17][18][19][20][21] and environmental and drug screening applications. 22,23 Integrated microfluidic devices for replacing traditional clinical tests have seen significant recent advances.…”
mentioning
confidence: 99%
“…20 With the aid of a simulation study, Yoon et al proposed a new way of measuring fluid interfacial nanoroughness through the morphological characteristics of graphene. 21 Microfluidic devices could also play important roles for environmental and drug screening applications. Liu et al reported a portable lab-on-a-chip system for detecting metal ions in water using gold nanoparticles.…”
mentioning
confidence: 99%